Party Autonomy, Separability, and Justice in Letter of Credit Dispute - Supriyadi, Mohammad Wangsit; Velentina, Rouli Anita; Kumar, Sanjeev; Chhachhar, Varun (UIR Press, 2026)
International commercial disputes frequently involve multiple interconnected yet legally independent agreements, including engineering, procurement, and construction (EPC) contracts, letters of credit (L/Cs), and bank account agreements. Although the principle of party autonomy permits contracting parties to select their preferred dispute resolution forum, conflicting jurisdiction clauses across related agreements create fragmented jurisdiction and legal uncertainty. This study examines the legal problem of determining the competent forum when forum selection clauses in interconnected contracts are inconsistent. Using a normative juridical method and a case study of Central Jakarta District Court Decision No. 362/Pdt.G/2017/PN Jkt.Pst., affirmed on appeal, cassation, and judicial review, the research analyzes judicial reasoning in resolving competing jurisdictional claims. The findings reveal that the court asserted jurisdiction by treating the L/C as an integral component of the EPC payment mechanism, thereby subordinating disputes arising from the L/C and related banking arrangements to the forum selection clause in the EPC contract. This reasoning overlooks the principles of party autonomy and the autonomy (separability) of letters of credit, potentially undermining legal certainty in international commercial transactions. The study contributes to private international law scholarship by proposing a more coherent framework for resolving fragmented jurisdiction through greater recognition of the separability principle and the independent legal character of banking instruments.